Effect of Multiple Gene Copy Number of Bacterial Lipase to Increase Lipase Production in Pichia pastoris - Puspitasari, Esti; Rustam, Yepy Hardi; Satya, Andreas Adhi; Suwanto, Antonius; Wahyudi, Aris Tri; Astuti, Rika Indri (Bogor Agricultural University, Indonesia, 2025)
Bacterial lipase poses potential challenges when expressed in eukaryotic protein expression systems such as Pichia pastoris. This research aims to increase extracellular T1.2RQ lipase secretion (free lipase) with multiple gene copy number strategies in Pichia pastoris and it was first performed on lipase from Geobacillus stearothermophilus T1.2. In this study, the T1.2RQ lipase gene from Geobacillus stearothermophilus T1.2 was expressed in Pichia pastoris GS115 through a strategy involving multiple copies of lipase, resulting in increased lipase activity. Three copies of the lipase gene in pPIC9K_T1.2RQ(3x) recombinant plasmid were integrated into the genome of Pichia pastoris GS115, and quantitative analysis using qPCR technique confirmed that the GS115 transformant strain contained six copies of T1.2RQ gene, indicating two integration events. Lipase activity measurement showed that the GS115/T1.2RQ(6x) strain exhibited a 111% increase compared to that containing a copy of the T1.2RQ gene. SDS-PAGE and Zymogram results showed a protein band with a size of 43kDa. Qualitative analysis in LA+TBN media of all strains containing the T1.2RQ gene showed clear zones. Lipase production in flask fermentation took at least 120 hours to produce the best lipase activity. Thus, strategies with multiple copy numbers of gene lipase have significantly increased the expression of the bacterial lipase gene in Pichia pastoris GS115.